PENGARUH LIKUIDITAS, RENTABILITAS, DAN LEVERAGE TERHADAP NILAI DIVIDEND PER SHARE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005-2011 - Emiati, Emiati; Arza, SE, M.Sc, AK, Fefri Indra; Ramayani, S.Pd, ME, Citra (Pendidikan Ekonomi, 2014)
ABSTRACTThe issues that examined in this research is whether there are significant of liquidities, rentabilities, and leverage toward in the dividend per share of value in manufacture company which registered to effect indonesia of stock exchange in period 2005-2011. This research have purpose for determine: 1) The liquidities have in fluence toward the dividend per share value in the manufacture company which registered in effect indonesia of stock exchange in period 2005-2011. 2) The rentabilities have in fluence toward the dividend per share value in the manufacture company which registered in effect indonesia of stock exchange in period 2005-2011. 3) The leverage have in fluence toward the dividend per share value in the manufacture company which registered in effect indonesia of stock exchange in period 2005-2011. 4) The liquidities, rentabilities, and leverage togerher toward et dividend per share value in manufacture company which that registered in effect of stock exchange in period 2005-2011. This kind of research is descriptive research and associative. The selecting of method sample is purposive sampling, so that can get the result 9 manufacture company that registered in effect indonesia of stock excange during the period 2005-2011. Â The result indicate that: 1) The liquidities have negative influence and significant to the dividend per share value with value sig 0,035 < Î± 0,1, it is mean that H01 is reject and Ha1 is accept. 2) The rentabilities has positive influence and significant toward the dividend per share value with value sig 0,000 < Î± 0,1, it is mean that H02 is reject Ha2 is accept. 3) The leverage have negative influence and significant toward dividend per share value with value sig 0,087 < Î± 0,1, it is mean that H03 is reject Ha3 is accept. 4) The liquidities, rentabilities, and leverage by do together have positive in fluenceÂ and significant toward dividend per share value with value sig 0,000 < Î± 0,1, it is mean that H04 is reject Ha4 is accept.